Correlation Between Glucosuria Positivity Values in Patients Diabetes Mellitus and The Incidence of Candiduria - Adhi Kumoro Setya; Ridwan Khoirudin (Jurnal Biologi Tropis, 2026)
Diabetes mellitus is a chronic disease characterized by persistent hyperglycemia and is associated with various complications, including opportunistic infections such as candiduria. Hyperglycemic conditions, glucose detected in urine (glucosuria) is presumed to provide a supportive environment for the growth of microorganisms, including Candida spp. The relationship between the degree of glucosuria positivity and the incidence of candiduria still requires further investigation. Therefore, this study aimed to analyze the association between the level of glucosuria positivity and the occurrence of candiduria among diabetes mellitus patients enrolled in the Chronic Disease Management Program (PROLANIS). This study employed an analytical design with a cross-sectional approach. Samples were selected using a purposive sampling technique based on predetermined inclusion criteria, resulting in 21 female respondents aged ≥45 years. Glucosuria examination was performed using the urine dipstick method based on the glucose oxidase–peroxidase enzymatic reaction principle. Urine culture was conducted on CHROMagar Candida (CAC) medium using the 100-conversion method to calculate colony counts, and candiduria was defined as colony growth ≥10³ CFU/mL. Data were analyzed using Fisher’s Exact Test.The results showed that most respondents had positive glucosuria with varying degrees, and the prevalence of candiduria was 66,6%. Statistical analysis indicated no significant association between the level of glucosuria positivity and the occurrence of candiduria 0,892 (p>0.05). In conclusion, glucosuria was not significantly associated with candiduria in the study population.